Complete genome sequence, metabolic model construction, and huangjiu application of Saccharopolyspora rosea A22, a thermophilic, high amylase and glucoamylase actinomycetes - Ma, Donglin; Liu, Shuangping; Han, Xiao; Nan, Mujia; Xu, Yuezheng; Qian, Bin; Wang, Lan; Mao, Jian (Frontiers in Microbiology, 2022)
Saccharopolyspora is an important microorganism in the fermentation process of wheat qu and huangjiu, yet the mechanisms by which it performs specific functions in huangjiu remain unclear. A strain with high amylase and glucoamylase activities was isolated from wheat qu and identified as Saccharopolyspora rosea (S. rosea) A22. We initially reported the whole genome sequence of S. rosea A22, which comprised a circular chromosome 6,562,638 bp in size with a GC content of 71.71%, and 6,118 protein-coding genes. A functional genomic analysis highlighted regulatory genes involved in adaptive mechanisms to harsh conditions, and in vitro experiments revealed that the growth of S. rosea A22 could be regulated in response to the stress condition. Based on whole-genome sequencing, the first genome-scale metabolic model of S. rosea A22 named iSR1310 was constructed to predict the growth ability on different media with 91% accuracy. Finally, S. rosea A22 was applied to huangjiu fermentation by inoculating raw wheat qu, and the results showed that the total higher alcohol content was reduced by 12.64% compared with the control group. This study has elucidated the tolerance mechanisms and enzyme-producing properties of S. rosea A22 at the genetic level, providing new insights into its application to huangjiu.